Factors Analysis of the Factors Affecting Customer Satisfaction on Accommodation Alternatives - Suvachart, Noppamash (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2017)
This study aimed to determine the factors contributing to customers’ decision in choosing an alternative accommodation. A questionnaire survey was carried out among randomly selected Thais aged 18 – 51 who have leisure traveling experience. A total of 520 questionnaires were distributed on May-June 2016. Out of the total sample of 520, only 488 completed responses were valid (with a response rate of about 93.8%). An exploratory factor analysis was conducted to identify selection factors adopted by Thais when they chose the alternative accommodation. The major findings revealed five factors in choosing an accommodation which were: (1) security, (2) recreational facilities, (3) local landscape, (4) availability of special services, and (5) nice host. Finally, the marketing implications and some suggestions were presented.